A multicentre analysis of abiraterone acetate in Canadian patients with metastatic castration resistant prostate cancer - Clayton, Ravinder; Wu, Jackson; Heng, Daniel Y; North, Scott A; Emmenegger, Urban; Hotte, Sebastien; Chi, Kim; Zielinski, Rob; Al-Shamsi, Humaid; Chen, Leo; Eigl, Bernhard (Canadian Urological Association Journal, 2014)
Introducton: The COU-AA-301 trial showed that abiraterone acetate (abiraterone), an oral cytochrome p450 CYP17 inhibitor, improved survival for men with metastatic castration-resistant prostate cancer (mCRPC) progressing after docetaxel. To better understand the non-clinical trial experience with abiraterone, we undertook a multicentre retrospective analysis of Canadian mCRPC patients treated with abiraterone. Methods: Consecutive patients with mCRPC who received abiraterone post-docetaxel were identified using centralized pharmacy records. These patients came from 5 Canadian tertiary cancer centres. Patients who received abiraterone for approved indications were included. Demographics, prognostic factors, treatment outcomes and adverse events were abstracted. Results: We included 187 patients who initiated abiraterone between January 2011 and June 2012. The median age at diagnosis and abiraterone start was 65 and 73 years, respectively. Seventy-three (39%) patients had metastatic disease at diagnosis. The Eastern Cooperative Oncology Group (ECOG) performance status of 0, 1, 2 and 3 was noted in 17, 96, 39 and 8 patients, respectively. The median prostate-specific antigen (PSA) at abiraterone start was 132, with a median PSA doubling time of 2.8 months. The median follow-up of patients still on active follow-up was 13 months. The proportion of patients achieving a ≥50% PSA reduction was 64/177 (36%). PSA progression-free survival was 3.5 months (95% confidence interval [CI], 3.0, 4.0). Median overall survival from start of abiraterone was 11 months (95% CI, 8.0, 13) and 38 months (95% CI, 31, 41) from date of mCRPC. Anemia and fatigue were the most commonly reported adverse events. Conclusions: This study carries the inherent limitations of a retrospective chart review. The outcomes in this series of men treated with abiraterone in a non-trial setting were expected, considering previous clinical trials. Our results, therefore, support the generalizability of the COU-AA-301 study results.